Integrating climate change into calcareous grassland management - Maalouf, Jean-Paul; Le Bagousse-Pinguet, Yoann; Marchand, Lilian; Bâchelier, Emilie; Touzard, Blaise; Michalet, Richard (The Journal of applied ecology, 2012)
1. Climate change is rarely taken into consideration in conservation management strategies aimed at protecting biodiversity from other threats. We examined the implications of this perspective in European calcareous grasslands, which are among the richest herbaceous systems of the continent and are therefore of high nature conservation interest. These systems are currently undergoing species loss because of the abandonment of agro-pastoral practices. Classic ecological theory assumes that conservation management activities (such as regular mowing) and drought events should increase diversity through decreased plant competition in abandoned mesic communities. In turn, this could reduce diversity in xeric communities although positive plant interactions (facilitation) might buffer these negative effects and maintain diversity. 2. We studied the effects of regular mowing and experimentally induced drought on diversity and biotic interactions between two transplanted species in mesic and xeric calcareous grasslands. The study sites in south-western France have not been subjected to any management for the last 30 years. 3. Drought did not affect mesic systems although mowing increased plant diversity through decreased competition. By contrast, mowing had no significant effect in xeric systems although drought decreased diversity. Interestingly, transplants were subject to neither competition nor facilitation in the xeric systems. 4. Synthesis and applications. Regular mowing and drought events impact plant diversity of mesic and xeric calcareous grassland communities in different ways. We recommend regular mowing of mesic grasslands, even in the context of climate change. By contrast, we recommend less-frequent mowing of xeric grasslands together with specific interventions such as assisted migration for species with poor drought tolerance. Similar studies in other ecosystems on larger spatial and temporal scales should examine the dual effects of management and climate change to identify appropriate management programmes.